Illegal Logging Criminal Investigation Process - Dwi Agus Istiyono (Universitas Islam Sultan Agung, 2020)
This study aims to determine the investigation process of illegal logging in the Rembang Police jurisdiction and to find out the obstacles and the resolution of the handling of these obstacles. Illegal logging is basically an activity that begins with logging the forest to get wood, transportation, to the sale of wood which is not in accordance with the rules or is illegal because it does not have an official permit from the competent authority. The approach method used is juridical empirical, descriptive analytical research specifications. The data used are secondary data. Data collection methods are library research and field studies. The data analysis method uses qualitative analysis. As a tool of analysis, law enforcement theory, legal certainty theory and structural functional theory are used. The results showed that the investigation process for illegal logging in the Rembang Police jurisdiction was carried out based on KUHAP and Perkap Polri No. 16 of 2019. The basis for the investigation was a report from Perhutani that had secured the perpetrators and evidence. Then a Police Report is prepared, which is then carried out to carry out an investigation. Obstacles in the enforcement of criminal law on illegal logging in the Rembang Police jurisdiction are obstacles from the law, the return of case files from the public prosecutor, requests for old expert witnesses and lack of legal awareness from the public. Resolutions in dealing with obstacles to criminal law enforcement against illegal logging crimes in the Rembang Police jurisdiction are completing the investigation process in accordance with procedures, completing the case files according to the instructions of the public prosecutor, waiting for expert witnesses to be present or conducting examinations at the location of expert witnesses, and coordinating with Perhutani and Bhabinkamtimas for socialization to the community.